DIFFICULTY FACTORS IN THE ACQUISITION OF MODIFIER VERBAL VOCABULARY OF JAPANESE LITERARY STUDY PROGRAM STUDENTS OF SEMESTER IV - I. Imelda (Universitas Sembilanbelas November Kolaka, 2017)
This study was conducted to identify and describe the difficulty in acquiring the vocabulary of Japanese verbs modifier, found in a matter of grammar training courses. This study used a quantitative approach and took 20 samples of students at the Japanese language Study Program at semester IV students, Universitas Hasanuddin Makassar. Forms of matter being tested consist of 40 questions categorized matching verb in the sentence. The 10 questions were each verb that functions as a modifier of the object, the subject, and the auxiliary verb and a verb that functions as a condition. Through this study showed that difficulties in acquiring student the vocabulary of verbs modifier due to a lack exercises that contain a variety of the vocabulary and verbs modifier, such verbs changes such as present, past, and forms like Joutai Doushi. It is also caused by the input of vocabulary and verbs use that tend to be static or does not develop only limited vocabulary and verbs that appear between chapters five through chapter 12 only. Students were more fixated on the familiar verbs vocabulary they use. Besides the use of Kanji without Furigana on the verb and the collocation of words also have contributed to the error occurred.